Tax Reform in Economies in Transition : A Brief Introduction to the Main Issues - Tanzi, Vito. (Washington, D.C. : International Monetary Fund, 1991)
The transition from a command to a market economy requires profound reforms of the tax system. Such a transition will put downward pressures on the level of taxation at a time when public expenditure remains high. This paper outlines the main characteristics of the tax systems in centrally-planned economies. It describes recent changes in those tax systems. Finally, it discusses the major difficulties that will be faced, and the errors that must be avoided, during the transition.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet